Analysis of Influencer Marketing Communication in Using the Live Feature on the Tiktok Application - Jentayu Jentayu; Sori Monang (Budapest International Research and Critics University, 2023)
The Indonesian Tiktok application is widely used for creativity and business by the community. Currently there are several influencer marketing who use the live feature to run their business with their own style of language or personal branding. Speech style is the use of the richness of a language by someone in speaking or writing. In addition, the use of certain varieties can also be interpreted as achieving certain effects or the general characteristics of the language of a literary group. The purpose of this study is to analyze influencer marketing communication strategies to attract customers through live tiktok functionality when doing business. This research method uses AIDA's essence theory (Awareness, Interest, Desire, and Action). The results of this study were obtained from the Tiktok account@ddhivaaaaa. The use of this research is not only to add insight and knowledge, but also to provide information about the use of the language-style Tiktok application for influencer marketing, especially in live functions.